RELIGIOUS MODERATION TO PREVENT RADICALISM IN ACEH ISLAMIC COLLEGE - Mawardi Mawardi (EMPIRISMA: JURNAL PEMIKIRAN DAN KEBUDAYAAN ISLAM, 2022)
Aceh, which has had the privilege of implementing sharia law in its territory, has faced a major challenge for accusations of "radicalism and extremism" from nationalists and Islamophobic groups who do not like the implementation of sharia law. It is as if by implementing sharia law in their territory the Acehnese are far from moderate Islam and cannot accept differences. However, this research proves that this is not true. Aceh is ideologically still dominated by moderate Islamic thought, as evidenced by PTKIN Aceh consistently promoting and disseminating moderate Islamic thought in the campus environment and the community in its area, with the continued increase in the number of religious moderation houses on PTKIN campuses, whose benefits are not only for the community. not only for academics but also for the surrounding community.